San Cipriano experimentado a través de las bebidas tradicionales y los ritmos (2019)
With the objective of diversifying the touristic offer from San Cipriano community a touristic experience was designed with a social innovation approach. A sustainable proposal was created, one that is based on the territory features as well as the cultural characteristics of the community that inhabits this natural reservation. Now a days, San Cipriano’s incomes are based on a 90% on ecotourism, which places its nature as its main attraction, leaving aside the invaluable cultural tradition represented in the gastronomy, believes and expressions. This is why the cultural experience proposed aims to use ethnotourism as a way to enhance the cultural believes within the community, which is an imminent necessity in order to prevent the growing fade into oblivion of the cultural traditions, specially from new generations. What the experience proposes is the generation of income by transforming the cultural believes into an ethnotouristic attraction, where the elders and the youths will strengthen traditional knowledge. The proposal was developed and co- created along with the community, through a long process where first hand research, field work within the context, high observation and inquiry’s where essential to think in a response that would respond San Cipriano community’s needs.